A Comparative Analysis of Safety and Efficacy of Different Methods of Tube Placement for Enteral Feeding Following Major Pancreatic Resection. A Non-Randomized Study - Abu-Hilal, Mohammad; Hemandas, Anil K; McPhail, Mark; Jain, Gaurav; Panagiotopoulou, Ioanna; Scibelli, Tina; Johnson, Colin D; Pearce, Neil W (JOP. Journal of the Pancreas, 2016)
Context Postoperative enteral nutrition is thought to reduce complications and speed recovery after pancreatic resection. There is little evidence on the best route for delivery of enteral nutrition. Currently we use percutaneous transperitoneal jejunostomy or percutaneous transperitoneal gastrojejunostomy, or the nasojejunal route to deliver enteral nutrition, according to surgeon preference. Objective To compare morbidity, efficiency, and safety of these three routes for enteral nutrition following pancreaticoduodenectomy. Patients Data were obtained from a prospectively maintained database, for all patients undergoing pancreatic resection between January 2007 and June 2008. One-hundred pancreatic resected patients underwent enteral nutrition: 93 had Whipple’s operations and 7 had total pancreatectomies. Intervention Enteral nutrition was delivered by agreed protocol, starting within 24 h of operation and increasing over 2-3 days to meet full nutritional requirement. Results Delivery route of enteral nutrition was: percutaneous transperitoneal jejunostomy in 25 (25%), percutaneous transperitoneal gastrojejunostomy in 32 (32%) and nasojejunal in 43 (43%). The incidence of catheter-related complications was higher in percutaneous techniques: 24% in percutaneous transperitoneal jejunostomy and 34% in percutaneous transperitoneal gastrojejunostomy as compared to nasojejunal technique (12%). Median time to complete establishment of oral intake was 14, 14 and 10 days in percutaneous transperitoneal jejunostomy, percutaneous transperitoneal gastrojejunostomy, and nasojejunal groups, respectively. Nasojejunal tubes were removed at median 11 days (mean 11.5 days) compared to 5-6 weeks for percutaneous transperitoneal jejunostomy and percutaneous transperitoneal gastrojejunostomy. Commonest catheter-related complication in the percutaneous transperitoneal jejunostomy and percutaneous transperitoneal gastrojejunostomy was blockage (n=6; 10.5%), followed by pain after removal of feeding tube at 5-6 weeks (n=5; 8.8%), whereas in the nasojejunal group it was blockage (n=3; 7.0%), followed by displacement (n=2; 4.7%). Two patients died postoperatively in this cohort, however, there were no catheter-related mortalities. Conclusion Enteral nutrition following pancreatic resection can be delivered in different ways. Nasojejunal feeding was associated with fewest and less serious complications. On current evidence surgeon preference is a reasonable way to decide enteral nutrition but a randomized controlled trial is needed to address this issue. Image: Southampton University Hospital. Southampton, United Kingdom.